Factor y^2-y-2

y^2-y-2 = (y-2)(y+1)

Question

Asked 11/7/2014 1:29:50 PM

Updated 11/8/2014 9:55:26 AM

1 Answer/Comment

Edited by yumdrea [11/8/2014 9:55:26 AM]

g
googletag.cmd.push(function() { googletag.display('div-gpt-ad-1564665647093-0'); });

Rating

8

y^2-y-2 = (y-2)(y+1)

Added 11/8/2014 9:48:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/8/2014 9:55:19 AM]

What is the middle term of the product of (5a - 7)(2a - 1)? **Weegy:** (5a - 7)(2a - 1) = 10a^2 - 5a - 14a + 7; = 10a^2 - 19a + 9; The middle term is: -19a **User:** Factor 5x 2 - 7x + 2. **User:** Factor 2x 2 + 7x + 3. **User:** Find the length and width of a rectangle with an area of 2x 2 + x - 3. **Weegy:** 8x^2 - 2x = 1; 8x^2 - 2x - 1= 0; (4x + 1)(2x - 1) = 0 (4x + 1) = 0; 4x = -1, x = -1/4 or (2x - 1) = 0; 2x = 1; x = 1/2 Solution set: {x = -1/4, x = 1/2} **User:** What is the product of (4x + 3)(-2x - 5)? (More)

Question

Updated 11/1/2014 4:13:34 AM

4 Answers/Comments

5x^2 - 7x + 2

= 5x^2 - 2x - 5x + 2

= (5x - 2)(x - 1)

= 5x^2 - 2x - 5x + 2

= (5x - 2)(x - 1)

Added 11/1/2014 4:07:33 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/1/2014 4:38:05 AM], Rated good by andrewpallarca

2x^2 + 7x + 3

= 2x^2 + x + 6x + 3

= (2x + 1)(x + 3)

= 2x^2 + x + 6x + 3

= (2x + 1)(x + 3)

Added 11/1/2014 4:08:39 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/1/2014 4:39:21 AM], Rated good by andrewpallarca

The length and width of a rectangle with an area of 2x^2 + x - 3 is 2x + 3 and x - 1 .

2x^2 + x - 3

= (2x + 3)(x - 1)

2x + 3 is the length ,x - 1 is the width

2x^2 + x - 3

= (2x + 3)(x - 1)

2x + 3 is the length ,x - 1 is the width

Added 11/1/2014 4:11:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/1/2014 4:39:47 AM], Rated good by andrewpallarca

(4x + 3)(-2x - 5)

= 4x*(-2x ) - 2x*3 + 4x*(-5) + 3*(-5)

= -8x^2 - 6x - 20x - 15

= -8x^2 - 26x - 15

= 4x*(-2x ) - 2x*3 + 4x*(-5) + 3*(-5)

= -8x^2 - 6x - 20x - 15

= -8x^2 - 26x - 15

Added 11/1/2014 4:13:34 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/1/2014 4:40:39 AM], Rated good by andrewpallarca

Thomas Paine wrote:
the Articles of Confederation
the Constitution
Common Sense **Weegy:** Thomas Paine wrote: Common Sense. **User:** Three weaknesses of the Continental Army were:
lack of purposelittle organizationlack of equipmentuntrained
(More)

Question

Not Answered

Updated 11/12/2014 11:00:20 PM

1 Answer/Comment

Three weaknesses of the Continental Army were: little organization, lack of equipment

and untrained soldiers.

and untrained soldiers.

Added 11/12/2014 11:00:20 PM

This answer has been confirmed as correct and helpful.

Three weaknesses of the Continental Army were:
lack of purpose little organization lack of equipment untrained
User: The Continental Congress proclaimed the hero at Saratoga was:
Charles Cornwallis
Nathaniel Greene
Horatio Gates
George Washington **Weegy:** Horatio Gates **User:** Congress adopted the ______ asking Parliament not to break from the colonies until a compromise could be worked out.
Olive Branch Petition
Virginia Plan
Treaty of Paris (More)

Question

Not Answered

Updated 11/12/2014 11:19:06 PM

1 Answer/Comment

Factor 360t + 10t3 - 120t2. User: Find the quotient.
(5ab - 10b2 + 15bc) ÷ 5b User: Find the quotient.
42j4k2 ÷ (-3j3k) **Weegy:** = 42j k /- 3j k)
= - 14jk
Answer: - 14jk **User:** Factor the following polynomial completely.
-x2y2 + x4 + 9y2 - 9x2
**User:** Find the quotient.
(6x2 - x - 40) ÷ (5 + 2x) **User:** Factor k2 + 13k + 12.
**User:** Simplify m - {n + [p - (m + n - p)]}. **User:** Find the product.
(n + 8)(n - 2) **User:** Factor the four-term polynomial.
pq - 3r + pr - 3q. **User:** Factor 9b2 - 4. **User:** Choose the product.
-7p3(4p2 + 3p - 1) **Weegy:** -7p3(4p2 3p - 1) = 7p3 - 84p6. Source: **User:** Divide x4 + 7 by x - 3. **Weegy:** (x^4 + 7) ? (x - 3) = x^3 + 3x^2 + 9x + 27 R. 88
to check:
(x^3 + 3x^2 + 9x + 27)(x - 3)
= x^4 - 81 + 88
= x^4 - 7 **User:** Choose the product.
(5x2 + 2x - 3)(x - 1)
**Weegy:** (5x^2 + 2x - 3)(x - 1) = 5x^3 - 5x^2 + 2x^2 - 2x - 3x + 3 = 5x^3 - 3x^2 - 5x + 3 **User:** Factor -2bk2 + 6bk - 2b. (More)

Question

Updated 11/4/2014 6:04:53 PM

5 Answers/Comments

360t + 10t^3 - 120t^2

= 10t(36 + t^2 - 12t)

= 10t(t - 6)^2

= 10t(t - 6)(t - 6)

= 10t(36 + t^2 - 12t)

= 10t(t - 6)^2

= 10t(t - 6)(t - 6)

Added 11/4/2014 6:00:54 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:38:25 AM]

(n + 8)(n - 2)

= n^2 + 8n - 2n - 16

= n^2 + 6n - 16

= n^2 + 8n - 2n - 16

= n^2 + 6n - 16

Added 11/4/2014 6:02:14 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:42:24 AM]

-7p^3(4p^2 + 3p - 1)

= -28p^5 - 21p^4 + 7p^3

= -28p^5 - 21p^4 + 7p^3

Added 11/4/2014 6:04:06 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:43:22 AM]

Select the correct difference.
-3z7 - (-5z7) **Weegy:** b: 8z14 **User:** Find the sum and choose the correct answer.
2n3 + 4n2 - 7 and -n3 + 8n - 9 **Weegy:** (2 n^3+4 n^2-7)+(-n^3+8 n-9) your answer is n^3+4 n^2+8 n-16 **User:** Find the greatest common factor of 15x2y3 and -18x3yz. **User:** Select the correct difference.
5d2 + 4d - 3 less 2d2 - 3d + 4
**Weegy:** (5d^2 + 4d - 3) - (2d^2 - 3d + 4) = 3d^2 + 7d - 7 **User:** Choose the product.
a3b2 · 4ab3
**User:** Factor p2 - 8p - 20. **User:** Factor 6x2 - 17x + 5.
**Weegy:** The factored form of 6x^2 - 17x + 5 is: (3x - 1)(2x - 5) **User:** Factor 25x2 + 10x + 1. **Weegy:** Factor
25x^2 + 10x + 1
(5x + 1)(5x +1) works as 5x*5x = 25^2 and 5x +5x = 10x
**User:** Factor 360t + 10t3 - 120t2.
(More)

Question

Updated 11/4/2014 6:18:42 PM

3 Answers/Comments

-3z^7 - (-5z^7)

= -3z^7 + 5z^7

= 2z^7

= -3z^7 + 5z^7

= 2z^7

Added 11/4/2014 6:15:33 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:11:22 AM]

p^2 - 8p - 20

= p^2 - 10p + 2p - 2*10

= (p - 10)(p + 2)

= p^2 - 10p + 2p - 2*10

= (p - 10)(p + 2)

Added 11/4/2014 6:17:16 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:12:10 AM]

360t + 10t^3 - 120t^2

= 10t(36 + t^2 - 12t)

= 10t(t - 6)^2

= 10t(t - 6)(t - 6)

= 10t(36 + t^2 - 12t)

= 10t(t - 6)^2

= 10t(t - 6)(t - 6)

Added 11/4/2014 6:18:42 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/5/2014 8:13:26 AM]

34,603,708

questions answered

There are no comments.